Leadership Tendencies of Pakistanis: Exploring Similarities and Differences based on Age and Gender - Mujtaba, Bahaudin G.; ., Naseem Habib (Journal of Economics and Behavioral Studies, 2011)
The management styles of people are influenced by their cultural contexts and urgency of completing tasks. For example, it is expected that people will get things done in a speedy manner when their jobs are on the line, but they will still try to minimize the negative impact to their relationships. To explore the leadership tendencies of working adults in the Pakistani workplace, this paper focused on comparing the leadership orientation of 232 respondents based on their age and gender. Pakistanis have a significantly higher score on task orientation. Their relationship orientation score is also on the moderately high range. The high score on both leadership dimensions reflects on their cultural orientation. Practical suggestions for expatriates and implications for future studies are presented.